Fiscal Reforms Vis-a-Vis Industrial Development in Madhya Pradesh during Post Economic Reforms Period - Vashisht, Ritu (SFIMAR Research Review, 2016)
Madhya Pradesh is endowed with rich resources, is centrally located in the country and has huge potential for industrial development, its level of industrial development is very poor and the state is reckoned among the industrially less developed states in India. The crucial question is: why is it so that the state is not attracting adequate investment, both foreign and domestic, in the industrial sector of the state economy. The two most important regional factors having considerable impact on industrial development are the industrial policy and the fiscal policy of the state. The major purpose of this research is to suggest an integration of the two policies for accelerated industrial development. One major constraint on industrial development is the inadequacy of infrastructure in terms of transport, power, communication, irrigation, warehousing and godowns. This needs a well-designed policy for infrastructure development, which has to be related to the industrial policy of the state. Another important requirement for industrial development is the availability of entrepreneurial talent and industrial culture, which can be promoted through human resource development. Thus we need such industrial and fiscal policies, which can overcome disabling factors and promote the enabling factors for industrial development.